Genetics 101 - Michael Windelspecht (Science 101., 2009)
A genetics overview containing an introduction to the field; articles on topics such as DNA, RNA editing, the genetic code, chromosome structure, gene therapy, and mutations; information on genetics innovations; a glossary; and an annotated list of resources.